Preparation method and application of photocatalytic hydrogen production preservative film

By combining the photocatalyst Pt/CN-HT with the food packaging film, a photocatalytic hydrogen production plastic wrap was prepared, which solved the problems of high material costs, potential toxicity and lack of obvious preservation effects in the existing food freshness preservation methods, and achieved efficient and environmentally friendly food freshness preservation effects.

CN119529347APending Publication Date: 2025-02-28QUANZHOU NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411836715.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the existing food preservation methods, the materials are costly, potentially toxic and the preservation effect is not obvious, especially when hydrogen is used, the operation is complicated and expensive.

Method used

The photocatalyst Pt/CN-HT is combined with the food packaging film, and a photocatalytic hydrogen production material is prepared by one-step calcination in situ reduction method. Combining the synergistic action of hydrogen and antibacterial film, a photocatalytic hydrogen production plastic wrap is prepared.

Benefits of technology

It realizes the generation of hydrogen concentrations that meet the food preservation requirements under short-term light, reduces material costs, improves the preservation effect, extends the shelf life of the food, and has good degradability properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529347A_ABST
    Figure CN119529347A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a photocatalytic hydrogen production preservative film, graphite carbonitride is used as a photocatalyst, fish scale gelatin and chitosan are used as a film substrate, and the prepared FSG / CS / Pt / CN-HT preservative film has excellent oxidation resistance, mechanical property and barrier property, and can realize efficient antibiosis and food preservation under sunlight radiation. The photocatalytic technology is expanded to the field of food preservation, a new application field is opened up for photocatalytic hydrogen production, a new thought is provided for developing biodegradable environment-friendly packaging materials, the food preservation performance is greatly improved through the preservative film, loss and global environment pollution after agricultural products are harvested can be reduced, and the preservative film is suitable for popularization and application. The economic value is higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of food packaging materials, and specifically relates to a preparation method and application of a hydrogen-producing cling film. Background Art

[0002] As the world's population grows rapidly, the pressure on ecosystems increases, and the agricultural sector faces huge challenges. Despite this, food waste from agriculture remains serious, with nearly one-third of food wasted before consumption. A major cause of food waste is that perishable foods spoil before they reach consumers, especially agricultural products such as fruits and vegetables, about half of which are wasted each year. Factors that contribute to this problem include physiological aging, pathological decay and physical damage.

[0003] In order to reduce food waste, it is crucial to develop a cost-effective and environmentally friendly way of preservation. At present, gas fumigation is a common method for fruit preservation, but the gases used, such as sulfur dioxide and nitric oxide, are toxic and harmful to humans and the environment, and the gases and residues left after use pose a significant risk to humans and the environment. Hydrogen, as a key small molecule gas, has multiple benefits such as antioxidant and anti-inflammatory, and has gradually emerged in the field of agricultural science, but its use process is complicated and costly. It is common to prepare hydrogen into hydrogen-rich water to treat agricultural products, but this operation is both hydrogen-consuming and time-consuming. In addition, hydrogen-rich water has a short half-life and is not suitable for large-scale preservation applications. In recent years, some researchers have found that fumigating kiwifruit with low concentrations of H2 can inhibit the production of ethylene and delay the ripening and aging of the fruit. However, H2 is a dangerous, flammable and explosive gas; it requires special equipment and technology to support it, is complex to operate, and is expensive to store and transport. The efficient, safe and economical application of hydrogen in the preservation of fruits and vegetables has become a challenge that needs to be solved.

[0004] Photocatalytic water decomposition to produce hydrogen provides an environmentally friendly and efficient solution for the agricultural sector. Using solar energy, water can be decomposed to produce hydrogen through photocatalysts such as titanium dioxide, cadmium sulfide and graphite carbon nitride, which can be used to preserve agricultural products. Graphite carbon nitride has broad application prospects in the fields of environment and energy due to its good chemical stability and low cost, but its photocatalytic activity is limited and can be improved through surface modification and metal attachment. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation method and application of a photocatalytic hydrogen-generating cling film, in order to solve the problems of expensive material costs, potential toxicity and unclear preservation effect in the field of food preservation.

[0006] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing a photocatalytic hydrogen-generating cling film comprises the following steps: (1) calcining melamine in a muffle furnace and then cooling it to room temperature to prepare CN; (2) Take 3 g of CN in 40 mL of hydrochloric acid, stir continuously at room temperature for 10 h, filter and wash with ultrapure water until the eluate is a neutral solution, then dry the filtered precipitate for 12 h and calcine it in a muffle furnace to obtain CN-HT; (3) 0.5 g CN-HT was mixed with 1 mL chloroplatinic acid solution and stirred for 12 h, 1 mol / L NaBH4 solution was added, and stirred for 3 h. The mixture was centrifuged, washed, and dried to obtain Pt / CN-HT. (4) Decalcify 40 g of fish scales with sodium hydroxide solution, filter, wash the decalcified fish scales with ultrapure water until the eluate is neutral, boil the decalcified fish scales, cool and centrifuge to obtain the supernatant, which is the FSG solution; (5) Take 2 g of chitosan and add it to 100 mL of acetic acid solution, stir thoroughly, then add an equal volume of FSG solution and mix to obtain FSG / CS solution; (6) Add Pt / CN-HT to FSG / CS solution, then add glycerol and stir evenly. After drying, FSG / CS / Pt / CN-HT film is obtained.

[0007] Furthermore, the calcination temperature in step (1) is 400-600° C. and the calcination time is 2-4 hours.

[0008] Furthermore, the concentration of the hydrochloric acid in step (2) is 1-3 mol / L, and the drying temperature is 80-200°C.

[0009] Furthermore, the calcination temperature in step (2) is 400-600°C and the calcination time is 2-8 hours.

[0010] Furthermore, the concentration of the chloroplatinic acid solution in step (3) is 1-10 mg / mL, and the volume of the added NaBH4 solution is 1-10 mL.

[0011] Furthermore, the concentration of the sodium hydroxide solution in step (5) is 0.01 to 0.2 mol / L, the decalcification time is 0.2 to 2 h, and the step of boiling the decalcified fish scales is to add 1000 mL of ultrapure water and boil the fish scales until the ultrapure water is 400 mL.

[0012] Furthermore, the weight of the glycerol in step (6) accounts for 0.1-2% of the total solution mass.

[0013] Furthermore, the mass concentration of Pt / CN-HT in step (6) is 0.1-2.5 mg / mL.

[0014] A photocatalytic hydrogen-generating cling film prepared by the above preparation method.

[0015] The above-mentioned photocatalytic hydrogen-generating cling film is used for preserving fruits and vegetables, wherein the fruits and vegetables are tomatoes or kiwis.

[0016] Beneficial effects of the present invention: (1) The present invention prepares Pt / CN-HT photocatalytic hydrogen production material by a one-step calcination in-situ reduction method, which can produce hydrogen concentration that meets the requirements of food preservation under short-term illumination. The process flow is simple, the cost is low, and resources are saved.

[0017] (2) The present invention utilizes the synergistic effect of hydrogen and antibacterial film to greatly improve the preservation effect of the obtained fresh-keeping film and extend the shelf life of food. In addition, the fish scale gelatin / chitosan (FSG / CS) film has good biodegradability and is environmentally friendly, and has broad application prospects for food preservation.

[0018] In summary, the present invention combines the photocatalyst Pt / CN-HT with the food packaging film, the preparation method is simple, the material precursor is environmentally friendly and easy to obtain, and the cost is low; the FSG / CS / Pt / CN-HT fresh-keeping film prepared by the present invention has excellent antioxidant, mechanical and barrier properties, and explores the application of hydrogen in the preservation of tomatoes and kiwis. The present invention expands the photocatalytic technology to the field of food preservation, greatly improves the performance of food preservation, and has great economic value. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 : XRD patterns of FSG / CS / Pt / CN-HT (Example 1), FSG / CS and FSG.

[0020] Figure 2 : Thermogravimetric images of FSG / CS / Pt / CN-HT (Example 1), FSG / CS and FSG.

[0021] Figure 3 : Light transmittance of FSG / CS / Pt / CN-HT (Example 1), FSG / CS and FSG.

[0022] Figure 4 : Mechanical properties test of FSG / CS / Pt / CN-HT (Example 1), FSG / CS and FSG.

[0023] Figure 5: Antibacterial performance test of FSG / CS / Pt / CN-HT (Example 1), FSG / CS and FSG against Escherichia coli and Staphylococcus aureus.

[0024] Figure 6 : Degradability test of FSG / CS / Pt / CN-HT (Example 1), FSG / CS and FSG.

[0025] Figure 7 : Hydrogen production performance test of FSG / CS / Pt / CN-HT (Example 1).

[0026] Figure 8 : Study on the fresh-keeping performance of the preservative film of the present invention on tomatoes (a) and kiwifruit (b).

[0027] Fig. 9 : Changes in weight (a), firmness (b) and ethylene production (c) of tomatoes during storage under different conditions.

[0028] Fig.10 : Changes in weight (a), firmness (b) and ethylene production (c) of kiwifruit during storage under different conditions. DETAILED DESCRIPTION

[0029] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0030] Example 1 (1) 5 g of melamine was calcined in a muffle furnace at 400 °C for 2 h and then cooled to room temperature to obtain CN; (2) Take 3 g of CN in 40 mL of HCl (3 mol / L) solution, stir continuously at room temperature for 10 h, filter, wash the precipitate with ultrapure water until the eluate is a neutral solution, and then dry the filtered precipitate at 100 °C for 12 h to obtain CN-H; then place CN-H in a muffle furnace at 400 °C and calcine for 2 h to obtain CN-HT; (3) Take 0.5 g CN-HT and 1 mL of chloroplatinic acid solution (2 mg / mL), mix and stir for 12 h, add 2 mL of NaBH4 solution (1 mol / L), stir for 3 h, centrifuge, wash, and dry at 120 °C for 12 h to obtain Pt / CN-HT; (4) Take 40 g of fish scales and decalcify them with 0.1 mol / L sodium hydroxide solution for 1 h. Filter and wash with ultrapure water until the eluate is neutral. Add 1000 mL of ultrapure water and boil the fish scales to 400 mL. After cooling, centrifuge at 8000 rpm for 5 min to obtain the supernatant, which is the FSG solution.

[0031] (5) Take 2 g of chitosan (CS) and add it to 100 mL of 1% acetic acid solution. Stir it thoroughly at 600 rpm for 30 min to obtain a CS solution. Add an equal volume of FSG solution and mix to obtain a FSG / CS solution. (6) Add 7.5 mg of Pt / CN-HT into 15 mL of FSG / CS solution, then add 0.3 mL of glycerol, stir at 600 rpm for 30 min, and dry at 50 °C for 4 h to form a FSG / CS / Pt / CN-HT film.

[0032] Example 2 (1) 5 g of melamine was calcined in a muffle furnace at 500 °C for 3 h and then cooled to room temperature to obtain CN; (2) Take 3 g of CN in 40 mL of HCl (3 mol / L) solution, stir continuously at room temperature for 10 h, filter, wash the precipitate with ultrapure water until the eluate is a neutral solution, then dry the filtered precipitate at 100 °C for 12 h. The sample is named CN-H. CN-H is placed in a muffle furnace at 400 °C and calcined for 2 h to obtain CN-HT. (3) Take 0.5 g CN-HT and 1 mL chloroplatinic acid solution (3 mg / mL), mix and stir for 12 h, then add 2 mL NaBH4 solution (1 mol / L), stir for 3 h, centrifuge, wash, and dry at 120 °C for 12 h to obtain Pt / CN-HT; (4) Take 40 g of fish scales and decalcify them with 0.2 mol / L sodium hydroxide solution for 1 h, filter them, wash them with ultrapure water until neutral, add 1000 mL of ultrapure water and boil the fish scales to 400 mL, cool them, and centrifuge them at 8000 rpm for 5 min to obtain the supernatant, which is the FSG solution; (5) Take 2 g of chitosan and add it to 100 mL of 1% acetic acid solution, stir it thoroughly at 600 rpm for 30 min to obtain CS solution, add an equal volume of FSG solution, and mix to obtain FSG / CS solution; (6) Add 2.5 mg of Pt / CN-HT into 5 mL of FSG / CS solution, then add 0.3 mL of glycerol, stir at 600 rpm for 30 min, and dry at 50 °C for 4 h to form a FSG / CS / Pt / CN-HT film.

[0033] Example 3 (1) 5 g of melamine was calcined in a muffle furnace at 600 °C for 3 h and then cooled to room temperature to obtain CN; (2) Take 3 g of CN in 40 mL of HCl (3 mol / L) solution, stir continuously at room temperature for 10 h, filter, wash the precipitate with ultrapure water until the eluate is a neutral solution, then dry the filtered precipitate at 100 °C for 12 h. The sample is named CN-H. CN-H is then placed in a muffle furnace at 400 °C and calcined for 2 h to obtain CN-HT. (3) Take 0.5 g CN-HT and 1 mL of chloroplatinic acid solution (3 mg / mL), mix and stir for 12 h, then add 2 mL of NaBH4 solution (1 mol / L), stir for 3 h, centrifuge, wash, and dry at 120 °C for 12 h to obtain Pt / CN-HT; (4) Take 40 g of fish scales and decalcify them with 0.1 mol / L sodium hydroxide solution for 2 h, filter, wash with ultrapure water until neutral, add 1000 mL of ultrapure water and boil the fish scales to 400 mL, cool and centrifuge at 8000 rpm for 5 min to obtain the supernatant, which is the FSG solution; (5) Take 2 g of chitosan and add it to 100 mL of 1% acetic acid solution, stir it thoroughly at 600 rpm for 30 min to obtain CS solution, add an equal volume of FSG solution, and mix to obtain FSG / CS solution; (6) Add 1.5 mg of Pt / CN-HT into 3 mL of FSG / CS solution, then add 0.3 mL of glycerol, stir at 600 rpm for 30 min, and dry at 50 °C for 4 h to form a FSG / CS / Pt / CN-HT film.

[0034] Example 4 (1) 5 g of melamine was calcined in a muffle furnace at 600 °C for 4 h and then cooled to room temperature to obtain CN; (2) Take 3 g of CN in 40 mL of HCl (3 mol / L) solution, stir continuously at room temperature for 10 h, filter, wash with ultrapure water until the eluate is a neutral solution, then dry the filtered precipitate at 100 °C for 12 h to obtain CN-H, and then place CN-H in a muffle furnace at 400 °C for calcination for 2 h to obtain CN-HT; (3) Take 0.5 g CN-HT and 1 mL of chloroplatinic acid solution (3 mg / mL), mix and stir for 12 h, add 2 mL of NaBH4 solution (1 mol / L), stir for 3 h, centrifuge, wash, and dry at 120 °C for 12 h to obtain Pt / CN-HT; (4) Take 40 g of fish scales and decalcify them with 0.1 mol / L sodium hydroxide solution for 2 h, filter, wash with ultrapure water until neutral, add 1000 mL of ultrapure water and boil the fish scales to 400 mL, cool and centrifuge at 8000 rpm for 5 min to obtain the supernatant, which is the FSG solution; (5) Take 2 g of chitosan and add it to 100 mL of 1% acetic acid solution, stir it thoroughly at 600 rpm for 30 min to obtain CS solution, add an equal volume of FSG solution, and mix to obtain FSG / CS solution; (6) Add 10 mg of Pt / CN-HT into 50 mL of FSG / CS solution, then add 1 mL of glycerol, stir at 600 rpm for 30 min, and dry at 50 °C for 4 h to form a FSG / CS / Pt / CN-HT film.

[0035] Comparative Example 1 Take 40 g of fish scales and decalcify them with 0.1 mol / L sodium hydroxide solution for 1 h, filter, wash with ultrapure water until neutral, add 1000 mL of ultrapure water and boil the fish scales to 400 mL, cool and centrifuge at 8000 rpm for 5 min to obtain the supernatant, which is the FSG solution; dry at 50 °C for 4 h to form an FSG film.

[0036] Comparative Example 2 Take 2 g of chitosan and add it to 100 mL of 1% acetic acid solution, stir it at 600 rpm for 30 min to obtain a CS solution, add an equal volume of the above-mentioned FSG solution, mix it to obtain a FSG / CS solution; dry it at 50 °C for 4 h to form a FSG / CS film.

[0037] The XRD spectrum of the fresh-keeping film obtained in Example is almost the same as that of the FSG film ( Figure 1 ). All films show broad peaks in the range of 2θ = 15 ~ 25◦, verifying the existence of amorphous structure.

[0038] Thermogravimetric curve of the fresh-keeping film obtained in the embodiment is as follows Figure 2 As shown. The weight loss of each group is divided into two steps. The initial weight loss occurring in the temperature range of 30~200 °C may be due to the evaporation of water. The second weight loss mainly occurs in the temperature range of 200~400 °C, which is due to the degradation of glycerol and the decomposition of FSG and CS. After exceeding 400 °C, no further mass loss is observed on the thermogravimetric curve, indicating the presence of non-combustible minerals in the cling film.

[0039] like Figure 3As shown, the transmittance of FSG and FSG / CS films in the near-ultraviolet and visible light bands is the highest, reflecting their weak UV blocking ability, but the transmittance in the visible light band is satisfactory. In contrast, the introduction of Pt / CN-HT nanomaterials in Example 1 significantly improves the shielding ability of the cling film against near-ultraviolet light, although it also leads to a decrease in some transmittance in the visible light region. The decrease in transmittance is mainly due to light scattering caused by the Pt / CN-HT nanocomposite material, and the final transmittance is maintained at around 35%.

[0040] The effect of Pt / CN-HT doped films on the tensile strength (TS) and elongation at break (EB) of the materials was studied. Figure 4 As shown. By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that since Pt / CN-HT is evenly distributed in the film, it fills the gaps inside the film, increases the contact area, and forms a tight connection with the film through strong hydrogen bonding interactions. This interaction inhibits phase separation and promotes effective stress transfer at the interface. Figure 4 As shown in Figure 3, the final TS and EB of the FSG / CS / Pt / CN-HT membrane are 25.79 MPa and 28.38%, respectively, which are significantly higher than those of the FSG membrane (16.08 MPa and 13.96%).

[0041] At the same time, the antibacterial properties of plastic wrap were also investigated. Figure 5 As shown. FSG membrane has no obvious inhibitory effect on Escherichia coli and Staphylococcus aureus. However, the CS component in the FSG / CS membrane can interfere with the physiological function of bacteria by adsorbing electronic substances in bacterial cells, thereby exerting an antibacterial effect, but its antibacterial effect on Escherichia coli is only 75.1%, and its antibacterial effect on Staphylococcus aureus is only 73.96%, which is not enough to meet the requirements of efficient antibacterial. CN has been proven to be an effective carrier of antibacterial materials. The present invention significantly improves its antibacterial properties by embedding Pt nanoparticles with rich catalytic sites into nanoporous CN-HT. The results show that the antibacterial rates of FSG / CS / Pt / CN-HT membrane against Escherichia coli and Staphylococcus aureus are 97.1% and 96.4%, respectively.

[0042] To further explore the degradation performance of the cling film, the prepared cling film FSG, FSG / CS and FSG / CS / Pt / CN-HT were buried in the soil, and the degradation was observed on the 0th, 1st, 2nd, 3rd, 4th and 5th day respectively. Figure 6 It can be seen that the fresh-keeping film prepared by the present invention has good degradation performance.

[0043] The hydrogen production performance of plastic wrap is as follows Figure 7As shown, in a 6 L closed container, the plastic wrap can produce 85 ppm of H2 when irradiated with a xenon lamp (power 300 W, irradiation wavelength greater than 420 nm) for 20 minutes, and it remains stable after three cycles.

[0044] Application Example 1 The tomatoes and kiwi fruits in the following application examples were purchased from a nearby store on the day of the experiment.

[0045] Tomatoes and kiwifruit were divided into four groups, namely, Control group, H2 group, FSG / CS / Pt / CN-HT group and H2+FSG / CS / Pt / CN-HT group. The Control group was not treated; the H2 group was fumigated with H2 at a concentration of 4.5 ppm; the FSG / CS / Pt / CN-HT group was wrapped with the FSG / CS / Pt / CN-HT cling film prepared in Example 1; the H2+FSG / CS / Pt / CN-HT group was wrapped with the FSG / CS / Pt / CN-HT cling film and irradiated with a xenon lamp (power 300 W, irradiation wavelength greater than 420 nm).

[0046] The four groups of fruits were placed in 6 L sealed boxes respectively, and the hydrogen concentration of the H2+FSG / CS / Pt / CN-HT group was monitored in real time using a hydrogen analyzer. When the hydrogen concentration reached 4.5 ppm, the xenon lamp irradiation was stopped, and the fruits were stored in this atmosphere for 24 h. After the hydrogen fumigation, all fruits were stored in an artificial climate chamber (25 ℃, 65% RH). The appearance of tomato and kiwi samples was observed on days 0, 3, 6, 9, 12, and 15, and the changes in their weight, hardness, and ethylene production were measured. The results are shown in Figure 2. Figure 8 As shown, the tomatoes and kiwifruit in the Control group shrank significantly after 15 days of storage, and mold appeared in the tomatoes in the Control group after 15 days. Compared with the preservation of fruits by H2 fumigation and FSG / CS / Pt / CN-HT plastic wrap alone, the preservation effect of tomatoes and kiwifruit was the best when the fruits were wrapped with FSG / CS / Pt / CN-HT plastic wrap and irradiated with a xenon lamp (power 300 W, irradiation wavelength greater than 420 nm). The results showed that the hydrogen produced by the FSG / CS / Pt / CN-HT plastic wrap under the irradiation of the xenon lamp can cooperate with the plastic wrap itself on the preservation effect of the fruit. After 15 days, the tomatoes and kiwifruit remained fresh. At the same time, the changes in the weight, hardness and ethylene production of tomatoes and kiwifruit during the preservation process were detected. The results are shown in Figure 9-10 As shown, the H2+FSG / CS / Pt / CN-HT group showed the best effect in weight reduction, hardness reduction and ethylene production.

[0047] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a photocatalytic hydrogen production cling film, characterized in that: The following steps are involved: (1) calcining melamine in a muffle furnace and then cooling it to room temperature to prepare CN; (2) Take 3 g of CN in 40 mL of hydrochloric acid, stir continuously at room temperature for 10 h, filter and wash with ultrapure water until the eluate is a neutral solution, then dry the filtered precipitate for 12 h and calcine it in a muffle furnace to obtain CN-HT; (3) 0.5 g CN-HT was mixed with 1 mL chloroplatinic acid solution and stirred for 12 h, 1 mol / L NaBH4 solution was added, and stirred for 3 h. The mixture was centrifuged, washed, and dried to obtain Pt / CN-HT. (4) Decalcify 40 g of fish scales with sodium hydroxide solution, filter, wash the decalcified fish scales with ultrapure water until the eluate is neutral, boil the decalcified fish scales, cool and centrifuge to obtain the supernatant, which is the FSG solution; (5) Take 2 g of chitosan and add it to 100 mL of acetic acid solution, stir thoroughly, then add an equal volume of FSG solution and mix to obtain FSG / CS solution; (6) Add Pt / CN-HT to FSG / CS solution, then add glycerol and stir evenly. After drying, FSG / CS / Pt / CN-HT film is obtained.

2. The preparation method according to claim 1, characterized in that: The calcination temperature in step (1) is 400-600°C and the calcination time is 2-4 hours.

3. The preparation method according to claim 1, characterized in that: The concentration of the hydrochloric acid in step (2) is 1-3 mol / L, and the drying temperature is 80-200°C.

4. The method for preparing a photocatalytic hydrogen cling film according to claim 1, characterized in that: The calcination temperature in step (2) is 400-600°C and the calcination time is 2-8 hours.

5. The preparation method according to claim 1, characterized in that: The concentration of the chloroplatinic acid solution in step (3) is 1-10 mg / mL, and the volume of the added NaBH4 solution is 1-10 mL.

6. The preparation method according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in step (5) is 0.01 to 0.2 mol / L, the decalcification time is 0.2 to 2 h, and the step of boiling the decalcified fish scales is to add 1000 mL of ultrapure water and boil the fish scales until the ultrapure water is 400 mL.

7. The preparation method according to claim 1, characterized in that: The weight of glycerol in step (6) accounts for 0.1-2% of the total solution mass.

8. The preparation method according to claim 1, characterized in that: The mass concentration of Pt / CN-HT in step (6) is 0.1-2.5 mg / mL.

9. A photocatalytic hydrogen-generating cling film prepared by any preparation method according to any one of claims 1 to 8.

10. The use of a photocatalytic hydrogen-generating cling film in the preservation of fruits and vegetables as claimed in claim 9, characterized in that: The fruits and vegetables are tomatoes or kiwis.